Redefining the Foreign Antigen and Self-Driven Memory CD4+ T-Cell Compartments via Transcriptomic, Phenotypic, and Functional Analyses - Kawabe, Takeshi; Ciucci, Thomas; Kim, Kwang Soon; Tayama, Shunichi; Kawajiri, Akihisa; Suzuki, Takumi; Tanaka, Riou; Ishii, Naoto; Jankovic, Dragana; Zhu, Jinfang; Sprent, Jonathan; Bosselut, Rémy; et al. (Frontiers in Immunology, 2022)
Under steady-state conditions, conventional CD4+ T lymphocytes are classically divided into naïve (CD44(lo) CD62L(hi)) and memory (CD44(hi) CD62L(lo)) cell compartments. While the latter population is presumed to comprise a mixture of distinct subpopulations of explicit foreign antigen (Ag)-specific “authentic” memory and foreign Ag-independent memory-phenotype (MP) cells, phenotypic markers differentially expressed in these two cell types have yet to be identified. Moreover, while MP cells themselves have been previously described as heterogeneous, it is unknown whether they consist of distinct subsets defined by marker expression. In this study we demonstrate using combined single cell RNA sequencing and flow cytometric approaches that self-driven MP CD4+ T lymphocytes are divided into CD127(hi) Sca1(lo), CD127(hi) Sca1(hi), CD127(lo) Sca1(hi), and CD127(lo) Sca1(lo) subpopulations that are Bcl2(lo) while foreign Ag-specific memory cells are CD127(hi) Sca1(hi) Bcl2(hi). We further show that amongst the four MP subsets, CD127(hi) Sca1(hi) lymphocytes represent the most mature and cell division-experienced subpopulation derived from peripheral naïve precursors. Finally, we provide evidence arguing that this MP subpopulation exerts the highest responsiveness to Th1-differentiating cytokines and can induce colitis. Together our findings define MP CD4+ T lymphocytes as a unique, self-driven population consisting of distinct subsets that differ from conventional foreign Ag-specific memory cells in marker expression and establish functional relevance for the mature subset of CD127(hi) Sca1(hi) MP cells.